Pengelolaan Program Bina Pribadi Islam di SMP IT Insan Cendekia Klaten - Aslim, Masriqa; Makruf, Imam (Center of Language and Cultural Studies, 2021)
Islamic schools make every effort to foster student personaliities according to the Qur’an through various programs, one of which is the Islamic Personal Development program. The purpose of this study was to analyze how to develop the personality of the Qur’an through the Islamic Personal Developmenr program at SMP IT Insan Cendekia Klaten. This research use desciptive qualitative approach. Methods of data collection were carried out by observation, interviews and documentation. The validity of the data by means of source triangulation was analyzed using the Interactivr Model of Miles and Huberman which includes data collection, data reduction, data presentation and conclusion drawing. Results show the Islamic Personal Development Program at SMP IT Insan Cendekia Klaten, namely a) Planning, namely setting goals, teaching staff, curriculum, schedules and materials as well as grouping students, b) organizing namely by forming an organizational structure with its role. c) mobilization, namely activities included in curriculum and activities outside the curriculum, d) coaching, namely by holding official meetings every Saturday and recommendations for learning materials e) evaluation, namely using adab values in form of descriptions to parents and f) development, namely grouping students according to character child.